Popular beliefs regarding the treatment of senile cataract - Edméa Rita Temporini; Newton Kara Junior; Newton Kara José; Nilo Holzchuh
OBJECTIVE: To identify popular beliefs regarding the treatment of senile cataract in patients enrolled in the community health programs on eye rehabilitation. METHODS: A cross-sectional survey was carried out using an interview questionnaire that was applied to 776 subjects drawn from a non-probabilistic sample in five cities of the state of São Paulo. The sample was made up of 47.2% males and 52.8% females, aged 50 to 96 years (average age 71.6 years). RESULTS: Of the total of subjects studied, 41.9% had never attended school, and 78.5% were no longer in the employment market. Most (85.1%) credited the sight restoration to cataract surgery. Among those unconvinced, 47.4% asserted that sight restoration depended only on God's will. A greater proportion of women than men (p 0.0000) believed in the association of cataract and menopause, maternity, and menstrual periods and they admitted using herbal and rose teas for treating cataract. CONCLUSIONS: Misbeliefs related to the causes and treatment of senile cataract were identified, most probably of sociocultural basis, indicating the need of education on the subject.